ANALISIS PENINGKATAN PENERIMAAN PAJAK REKLAME DI KOTA SEMARANG - Nurbintara, Ayusari Teni; Larasati, Endang; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Regional Income is an areas income earned by local regulations in accordance with the legislation. Fluctuations in tax revenues indicate a problem in the implementation of development. The purpose of this study was to analyze management and Local Revenue enhancement strategy Semarang through advertisement tax and the factors that influence the acceptance of advertisement tax in Semarang. This study analyzes management of advertisement tax and factors that influence the government revenue in Semarang. The method used in this research is descriptive qualitative method. Data collection techniques used in this study by the method of field studies (interviews, observation and documentation) sampling method informant used purposive random sampling. Analysis of the data used is to use a SWOT analysis to determine the strengths, weaknesses, opportunities and threats in the advertisement tax collection. Results from the study showed that the planning concept is still weak and analyzing the potential, challenges and constraints in the management of the to increase advertisement tax. The strategies carried out in terms of intensification taxation namely simplification of administrative processes and stronger law enforcement are required. The etending taxation are increasing tax amount and taxed objects.